(untitled) (Research, Society and Development, 2022)
This study aimed to develop a diagnosis of land use suitability, growth prospects and milk production intensification in a family farm located in Conceição do Tocantins, Tocantins, Brazil. Data were obtained through interviews with employees and residents, cooperative members, analysis of productive activities and sources of income. To understand the milk production intensification, an experiment was carried out with the division of an area of ​​1 ha into 3 paddocks and pasture management. For soil aptitude characterization, vector data provided by Seplan were used. The division of the area into paddocks and pasture management allowed an increase in the animal load of 3 AUha-1year-1 and 48% in the daily milk production in the winter and 32% in the summer. In view of the results, it could be concluded that well-formed areas, rest and occupation period with grass reached animal load of 10 AUha-1year-1. Thus, the possibilities of agroecological intensification of pastures were promising and productive; however, investments were high. For professionals interested in these changes, it is necessary to invest in quality paddocks and cattle, in addition to professional training.